¿AUTONOMÍA O ESCUDO PROTECTOR?: EL MOVIMIENTO OBRERO Y POPULAR Y LOS MECANISMOS DE CONCILIACIÓN Y ARBITRAJE (CHILE, 1900-1924) - Sergio Grez Toso (Historia (Santiago), 2002)
This study explores the attitudes and positions assumed by the Chilean working classes during the first quarter of the 20th century with regard to the mechanisms of conciliation and arbitration that grew initially in a partly or completely spontaneous manner and then ever-increasingly encouraged by State authorities. The main focus of this article is the labour movement, but the viewpoints of both the State and employers are also analysed. After thorough examination of numerous social conflicts in which these mechanisms were implemented or where an attempt was made to put them into effect, the present work concludes that when the new legislation for labour relations appeared in the mid-1920s, it was favourably received, the fruit of long years of speeches and "field trials". Although the labour relation laws implemented in 1924 were the political elite’s answer to their need for order and social control, they also reflected the aspirations of vast sectors of the labouring classes -most probably the majority- who saw the action of the public authorities as a protection against employers abuse. However, obtaining the adherence of the working classes to the mediation policies of the State was not an easy task and was only possible after a long and contradictory debate within the popular and labour movement. This article attempts to reconstruct this process.